Design of Footwear Storage Control System with Fingerprint Based on Microcontroller - Alhafizh, Ahmad Abrar; Erlina, Tati (CHIPSET, 2025)
The issue of misplaced and stolen footwear in public spaces is a frequent problem that causes inconvenience to many people. This thesis aims to design and implement a smart locker system for footwear storage that uses biometric fingerprint security and is controlled by a microcontroller. The system integrates several key components: an AS608 fingerprint sensor for user authentication, an HC-SR04 ultrasonic sensor to detect if the locker is occupied, and an SW-420 vibration sensor to detect suspicious activity, such as forced entry. An ESP32 microcontroller serves as the central control unit, processing data from all sensors and managing the solenoid lock mechanisms via relays. Additionally, the system sends security alerts through a Telegram bot to the administrator. Based on the test results, the system successfully performs all its functions. The fingerprint sensor accurately handles both enrollment and matching processes. The ultrasonic sensor automatically and accurately detects the locker's status (empty/occupied). The vibration sensor effectively sends alert notifications when suspicious vibrations are detected. In conclusion, the implemented system is proven to be functional and an effective solution for improving the security and convenience of footwear storage in public areas.